The effect of Allium sativum (Garlic) extract on infectious bronchitis virus in specific pathogen free embryonic egg - Tabassom Mohajer Shojaei; Arash Ghalyanchilangeroudi; Vahid Karimi; Abbas Barin; Naser Sadri (Mashhad University of Medical Sciences, 2016)
Objective: Garlic is a plant has been used as a flavor, and anti-microbial and anti-diarrheal agent. Infectious bronchitis virus (IBV) is a coronavirus. The available vaccines against IBV cannot cover new variants. This study evaluated the inhibitory effects of garlic extract on IBV.  Materials and Methods: The constituents of garlic extract were detected by gas chromatography. This study was done in four groups of embryonic SPF eggs; first group was used for virus titration; second group received the mixture of different virus titration and constant amount of garlic extract; third group received 10-3 titration of virus and after 8 hr received garlic extract and the last group received different dilutions of garlic extract. Results: Based on our results, in the second group, IBV vaccine strain (4/91) at all titration and M41 in 10-2 and 10-3 titration and in the third group both variants of virus the embryonic Index (EI) was significantly increased. Conclusion: The garlic extract had inhibitory effects on IBV in the chickens embryo.